Potensi Ekstrak Daun Insulin (Tithonia diversifolia (Hemsl.) A. Gray) Terhadap Profil Kadar Glukosa Darah, Kadar Malondialdehid dan Histologi Islet Langerhans Pankreas Tikus Putih (Rattus norvegicus L.) Hiperglikemik - Anisa Rachma Sari; Tyas Rini Saraswati; Enny Yusuf Wachidah Yuniwarti (Faculty of Agricultural Technology, Universitas Semarang, 2021)
Diabetes mellitus is a degenerative disease with high risk. This disease can be caused by an increase in free radicals in the body. Free radicals in the body can be detected by testing malondialdehyde levels. The increase in free radicals can cause damage to the pancreatic islet Langerhans so that insulin ability is reduced. The reduced ability of insulin causes hyperglycemic conditions, which are the first symptoms of DM. The use of medicinal plants is widely used by the community as an alternative treatment for this disease. The insulin leaf plant (Tithonia diversifolia) is empirically used by the public as an antihyperglycemic drug. The aim of this study was to examine the ability of insulin and glibenclamide leaf extracts to reduce the level of free radicals in hyperglycemic conditions and to describe their ability to repair Langerhans islets damaged by toxic substances so that the blood glucose levels of hyperglycemic rats could return to normal. Hyperglycemic rats were obtained by injecting alloxan monohydrate at a dose of 150 mg/ BW of rats into male Rattus norvegicus intraperitoneally. This study used a completely randomized design (CRD), with four treatments with five replications each, namely group P1 as control mice, group P2 as hyperglycemic rats given 10 mg/ BW dose of glibenclamide/day, group P3 as hyperglycemic rats. who were given insulin leaf extract at a dose of 150 mg/ BW rats /day and group P4 as hyperglycemic rats who were given insulin leaf extract at a dose of 300 mg/ BW rats /day. The results showed that the administration of insulin leaf extract at a dose of 300 mg/ BW for rats/day was able to make blood glucose levels significantly different, but the malondialdehyde levels were not significantly different than control rats. In addition, administration of insulin leaf extract at a dose of 300 mg/ BW rats/day to hyperglycemic rats was also able to improve the condition of the Langerhans pancreatic islet towards conditions like control rats. The improvement in the condition of Langerhans pancreatic islet is indicated by the cell nucleus that is colored dark blue with more regular shapes.